Salbutamol Residue in Plasma and Urine of Balinese Calves after Single-Dose Administration - Yessy Anastasia; Hadri Latif; Lina Noviyanti Sutardi; Raphaella widiastuti (Acta VETERINARIA Indonesiana, 2021)
Salbutamol, a short-acting β2-adrenergic receptor agonist, due to illegal use in animal feed, is very dangerous for the safety of animal origin products. The purpose of this study is to determine the residue of salbutamol in plasma and urine of balinese calf after a single-dose administration. Three calves were given of feed fortification of salbutamol (10 mg/kg body weight). The salbutamol concentrations were measured in the plasma and urine. Samples were extracted with perchloric acid and purified by cation exchange solid phase extraction (SPE), then analyzed by High-Performance Liquid Chromatography (HPLC) with a photodiode array detector using an RP C18 column with a mixed mobile phase of purified water pH 3.0 (adjusted with phosphoric acid) and acetonitrile (90:10, v/v). The highest salbutamol concentration in the plasma sample was 0.28±0.15 μg/mL at 12 hours and decreased after 24 hours after feeding. The highest concentration of salbutamol in urine was 15.85±4.42 μg/mL at 18 hours and decreased gradually starting at 24 hours. This result concluded that salbutamol residues mostly excreted in the urine, and the highest salbutamol residues in plasma samples formed faster but also decreased more rapidly than residues formed in urine. The residue formed in plasma is lower than that in the urine.